SCIDOT-04. REPLACEMENT OF MICROGLIA BY BRAIN-ENGRAFTED MACROPHAGES PREVENTS MEMORY DEFICITS AFTER THERAPEUTIC WHOLE-BRAIN IRRADIATION. (11th November 2019) - Feng, Xi; Gupta, Sonali; Chen, David; Boosalis, Zoe; Liu, Sharon; Gupta, Nalin; Rosi, Susanna
Abstract: Microglia have a distinct origin compared to blood circulating myeloid cells. Under normal physiological conditions, microglia are maintained by self-renewal, independent of hematopoietic progenitors. Following genetic or pharmacologic depletion, newborn microglia derive from the local residual pool and quickly repopulate the entire brain. The depletion of brain resident microglia during therapeutic whole-brain irradiation fully prevents irradiation-induced synaptic loss and recognition memory deficits but the mechanisms driving these protective effects are unknown. Here, we demonstrate that after CSF-1R inhibitor-mediated microglia depletion and therapeutic whole-brain irradiation, circulating monocytes engraft into the brain and replace the microglia pool. These monocyte-derived brain-engrafted macrophages have reduced phagocytic activity compared to microglia from irradiated brains, but similar to locally repopulated microglia without brain irradiation. Transcriptome comparisons reveal that brain-engrafted macrophages have both monocyte and embryonic microglia signatures. These results suggest that monocyte-derived brain-engrafted macrophages represent a novel therapeutic avenue for the treatment of brain radiotherapy-induced cognitive deficits.